2008
DOI: 10.1002/uog.5310
|View full text |Cite
|
Sign up to set email alerts
|

Is severe macrosomia manifested at 11–14 weeks of gestation?

Abstract: Objective To determine the association between fetal biometry in the first or early second trimester and severe macrosomia at delivery. (mean, 6.66 ± 4.78 mm vs. 1.17 ± 4.6 mm, P < 0.0001 and 3 ± 2.2 days vs. 0.5 ± 2.3 days, P < 0.0001, respectively). Furthermore, there were significant correlations between the extent of macrosomia and the discrepancy between expected and measured fetal size at the time of NT screening (r = 0.47, P < 0.01 and r = 0.48, P < 0.01, respectively). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
5
17
0
3
Order By: Relevance
“…This is in keeping with previous studies showing a higher risk of intrauterine growth restriction in fetuses smaller than expected in the first trimester 15,16,20 . However, to our knowledge, only one small retrospective case–control study, with 30 cases of macrosomia and 60 controls, has shown a larger than expected CRL in the first trimester; moreover, expected CRL was related to last menstrual period in most cases 28 . Our findings add to the growing body of evidence suggesting that birth size may be influenced by disturbances that occur in the first weeks of gestation.…”
Section: Discussionsupporting
confidence: 91%
“…This is in keeping with previous studies showing a higher risk of intrauterine growth restriction in fetuses smaller than expected in the first trimester 15,16,20 . However, to our knowledge, only one small retrospective case–control study, with 30 cases of macrosomia and 60 controls, has shown a larger than expected CRL in the first trimester; moreover, expected CRL was related to last menstrual period in most cases 28 . Our findings add to the growing body of evidence suggesting that birth size may be influenced by disturbances that occur in the first weeks of gestation.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies suggested a correlation between measurements of CRL and birth weights in both singleton and twin pregnancies, assuming that abnormal fetal growth of some fetuses can be detected early in the fi rst trimester [4,9,13] . Other studies raised the possibility of an association between NT and birth weight, based on the hypothesis that hyperglycemia may cause both measurements to be increased with the proposed mechanisms of enhancement of microvascular permeability that increases NT and elevation of fetal insulin levels that increases birth weight [3,14,15,22] .…”
Section: Introductionmentioning
confidence: 98%
“…Hackmon et al [13] performed a case-control study of macrosomic infants and found that their CRL measurements were more often larger than expected based on prior pregnancy dating than the normal birth weight group. Poon et al [14] approached first trimester prediction of macrosomia by comparison of maternal risk factors, nuchal translucency measurement, and the serum analytes PAPP-A and hCG between pregnancies with macrosomic infants versus those with normal weight.…”
Section: Screening For Adverse Pregnancy Outcomesmentioning
confidence: 96%